Distribusi Ameloblastoma Berdasarkan Usia, Jenis Kelamin, Lokasi dan Subtipe Histopatologi di RSUD A.W. Sjahranie Samarinda Tahun 2015-2020: Distribution of Ameloblastoma Based on Age, Gender, Location and Histopathology at RSUD A. W. Sjahranie Samarinda in the Period of 2015-2020 - Sarah Prinadira; Cristiani Nadya Pramasari; Syahril Samad (Jurnal Sains dan Kesehatan, 2022)
Ameloblastoma is one of the most common benign tumors of the oral cavity originating from odontogenic epithelium. This tumor is slow-growing but aggressive, locally invasive, has a high potential for recurrence, transforms into malignant and metastasizes. Risk factors such as tumor location, tumor size, patient age, radiographic appearance, a histopathology subtype, and selection of appropriate treatment correlate with recurrence in ameloblastoma. This study aimed to determine the distribution of ameloblastoma based on age, gender, location, and histopathology subtype. This research is quantitative research with a descriptive method using medical record data subjects and paraffin slides/blocks based on predetermined inclusion criteria. Data were grouped by age, gender, location and histopathology subtype. The results are presented in the form of tables and narratives. Based on the data obtained from 27 samples in this study, the age range category of 45-54 years was the age group with the most ameloblastoma found in 11 patients (40.74%). The number of males patients was 13 patients (48.15%) and 14 patients (51.95%) found on females. Most ameloblastomas were found in the mandible, with a total of 26 patients (96.30%). The most common histopathology subtypes were follicular and plexiform histopathology subtypes with 8 patients (29.63%) each.